2010
DOI: 10.1128/jb.00445-10
|View full text |Cite
|
Sign up to set email alerts
|

Human Hypervirulent Clostridium difficile Strains Exhibit Increased Sporulation as Well as Robust Toxin Production

Abstract: Toxigenic Clostridium difficile strains produce two toxins (TcdA and TcdB) during the stationary phase of growth and are the leading cause of antibiotic-associated diarrhea. C. difficile isolates of the molecular type NAP1/027/BI have been associated with severe disease and hospital outbreaks worldwide. It has been suggested that these "hypervirulent" strains produce larger amounts of toxin and that a mutation in a putative negative regulator (TcdC) allows toxin production at all growth phases. To rigorously e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
235
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(266 citation statements)
references
References 40 publications
24
235
5
Order By: Relevance
“…We define hypervirulent strains as those that are associated with more severe clinical disease. In addition to the production of toxin A (TcdA) and toxin B (TcdB), the presence of binary toxin (CdtA and CdtB), altered antimicrobial resistance patterns and increased sporulation capacity can contribute to the virulence of certain C. difficile strains (Akerlund et al, 2008;Lyras et al, 2009;Merrigan et al, 2010;Schwan et al, 2009;Voth & Ballard, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…We define hypervirulent strains as those that are associated with more severe clinical disease. In addition to the production of toxin A (TcdA) and toxin B (TcdB), the presence of binary toxin (CdtA and CdtB), altered antimicrobial resistance patterns and increased sporulation capacity can contribute to the virulence of certain C. difficile strains (Akerlund et al, 2008;Lyras et al, 2009;Merrigan et al, 2010;Schwan et al, 2009;Voth & Ballard, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Merrigan et al observed that some hypervirulent strains underwent early sporulation and produced large amounts of toxin, with greater efficiency than other strains. These researchers concluded that sporulation could contribute to the dissemination of infectious particles in the environment, thus helping toxins to confer adaptive advantages in the pathogenesis of hypervirulent strains of C. difficile [13].…”
Section: Persistence Of Sporesmentioning
confidence: 99%
“…These researchers have classified the tcd genes in two groups, one comprising A, B, D and E, and the other comprising C (as tcdC has the opposite orientation). It has also been found that tcdC is expressed in the exponential growth phase of the bacterium, while the other genes are expressed in the stationary phase [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Hypervirulent strains such as the molecular type NAP1/027/BI, have been found to have more robust toxin production and show an earlier spore-formation than other strains thus causing more severe infections. [119] Excessive toxin production in this strain has been traced to a mutation in the Toxin B encoding gene sequence. [120] Another emerging strain is the PCR ribotype 078, which is associated with community-associated C.difficile infection and has been isolated in animal and food products.…”
Section: Clostridium Difficile Infectionmentioning
confidence: 99%